Implication of Education in Acculturating Culture of Mambabei An A'Uhaidao Village, Aralle District, Mama’sa Regency, West Sulawesi - Ahdar; Abdul Halik; Musyarif (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2021)
Acculturation is a form of cultural change caused by contact or cultural groups, which emphasizes the acceptance of new cultural patterns and characteristics of indigenous peoples by minority groups. The acculturation of Islamic culture and local culture in Mambabei Ana' culture gave birth to various social values ​​in the social interactions of the community. Mambabei Ana' culture is an example of associative social interaction that leads to unity and cooperation in society. The research method used in this thesis is descriptive qualitative research. The data in this study were obtained from primary data and secondary data. Data collection techniques were carried out through observation, interviews and documentation, equipped with technical data analysis using data reduction, presentation and verification. The results of this study indicate that: 1) The implementation of the Mambabei Ana' culture in Uhaidao Village, Aralle District, Mamasa Regency is carried out with several ceremonial activities through three stages, namely the preparation stage (mappaissang, mokaju, ma'baje/sokko, and ma'bungkungkus); implementation stage (pegereang beke, pegereang manu, pambeengang sanga, and pa'bacaang barazanji); and the closing stage (ma'tarakang, and pambacaang prayer). 2) There are several social values ​​that exist in the acculturation of Mambabei Ana' culture, Uhaidao Village, Aralle District, Mamasa Regency, namely mutual cooperation, mutual assistance, togetherness, compassion, unity and praying for each other. 3) The implications of social education in acculturating Mambaaei Ana' culture, Uhaidao Village, Aralle District, Mamasa Regency, namely education on social awareness, social harmony,